2020
DOI: 10.3390/cancers12010188
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Profiling of piRNAs in Colorectal Cancer Identifies Consistent Overexpression of piR-24000 That Correlates Clinically with an Aggressive Disease Phenotype

Abstract: Piwi-interacting RNAs (piRNAs) represent a novel class of small non-coding RNAs (ncRNAs) that have been shown to have a deregulated expression in several cancers, although their clinical significance in colorectal cancer (CRC) remains unclear. With an aim of delineating the piRNA distribution in CRC, we conducted a systematic discovery and validation of piRNAs within two clinical cohorts. In the discovery phase, we profiled tumor and adjacent normal tissues from 18 CRC patients by deep sequencing and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Recent studies have shown that the expression of piRNAs is frequently deregulated in different types of cancers including CRC [ 81 ]. Because of their small size, high stability, and ease of detection, piRNAs represent a strong diagnostic and predictive biomarker [ 82 ] with high potential as CRC screening tools.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the expression of piRNAs is frequently deregulated in different types of cancers including CRC [ 81 ]. Because of their small size, high stability, and ease of detection, piRNAs represent a strong diagnostic and predictive biomarker [ 82 ] with high potential as CRC screening tools.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, the well-known piRNA piR-651 was found to be a potential marker for gastric cancer diagnosis [ 16 ]. In colorectal cancer, piR-24000 acts as a possible oncogene that can significantly distinguish patients with colorectal cancer from normal individuals [ 13 ]. Additionally, serum piR-54265, piR-020619, and piR-020450 were also found to serve as sensitive and specific noninvasive biomarkers for early colorectal cancer detection in previous studies [ 104 , 107 ].…”
Section: Pirnas As Diagnostic and Prognostic Biomarkers In Cancermentioning
confidence: 99%
“…Moreover, piR-24000 overexpression had a positive but not significant association with advanced nodal metastasis and with advanced tumor invasion. These data suggest that piR-24000 may constitute an oncogene in CRC that could act as a diagnostic or prognostic biomarker or as a therapeutic target in this malignancy [ 70 ].…”
Section: The Role Of Pirnas In Gastrointestinal (Gi) Cancersmentioning
confidence: 99%